123k views
3 votes
(Please help) Solve.

-4+4(-8+2n) = -37+8n

User BTC
by
5.6k points

2 Answers

1 vote

Answer:

No solution

Explanation:

-4 + 4(-8 + 2n) = -37 + 8n

-4 - 32 + 8n = -37 + 8n

-36 + 8n = -37 + 8n

8n - 8n = -37 + 36

0 = -1

Since 0 does not equal 1, this is a “No Solution”

4 votes

Answer:

No solutions for n

Explanation:

Distribute the 4 to the -8 and the 2n

-4 + 4*-8 + 4*2n = -37 + 8n

Multiply

-4 - 32 + 8n = -37 + 8n

Subtract 8n on both sides

-4 - 32 = -37

Subtract on the left

-36 = -37

No solutions because -36 does not equal -37

User Shoeb Mirza
by
5.7k points